2021
DOI: 10.4103/aca.aca_84_19
|View full text |Cite
|
Sign up to set email alerts
|

The synergistic effect of tranexamic acid and ethamsylate combination on blood loss in pediatric cardiac surgery

Abstract: Background: Pediatric patients are at risk for bleeding after cardiac surgery. Administration of antifibrinolytic agents reduces postoperative blood loss. Objective: Evaluation of the efficacy of combined administration of tranexamic acid (TXA) and ethamsylate in the reduction of postoperative blood loss in pediatric cardiac surgery. Methods: This prospective randomized study included 126 children submitted for cardiac surgery, and they were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…While oxytocin increases muscular uterine contractility and thus reduces bleeding [ 34 ]. Both tranexamic acid and ethamsylate are cost-effective drugs and give a synergistic impact than tranexamic acid alone [ 18 , 35 ]. A previous randomized control trial showed that the tranexamic acid and ethamsylate combination had a synergetic effect on decreasing post-operative bleeding when administrated in pediatric cardiac surgery [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…While oxytocin increases muscular uterine contractility and thus reduces bleeding [ 34 ]. Both tranexamic acid and ethamsylate are cost-effective drugs and give a synergistic impact than tranexamic acid alone [ 18 , 35 ]. A previous randomized control trial showed that the tranexamic acid and ethamsylate combination had a synergetic effect on decreasing post-operative bleeding when administrated in pediatric cardiac surgery [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eth and TXA exhibit a synergistic effect in hemostasis when administered intravenously together. This combined approach proves effectively minimizes intra-and postoperative blood loss [12].…”
Section: Discussionmentioning
confidence: 88%
“…TXA and ethamsylate (TXAEth) complement each other in hemostasis. Administering both intravenously could synergistically reduce intra-and postoperative blood loss [12]. The comparative effectiveness between oxytocin alone and the combined use of TXA and Eth remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…TXA is most frequently used in the treatment of idiopathic menorrhagia and pregnancy-related bleeding (threatened abortion and placenta previa) in obstetric and gynecologic therapy (24) .…”
Section: Discussionmentioning
confidence: 99%